Punctuation and Connecting Words in Croatian Text-Segmentation Model - Tuđman, Miroslav (Array, 1996)
In this paper the role of punctuation and connecting words named text indicators in order to obtain the Croatian Text Segmentation Model has been explored. It has been developed as a model which is supposed to be the basis of an approach to solving many NLP tasks.